Analysis of fatwa no. 83 of 2023 regarding the boycott of zionist Israeli products from the perspective of sadd al-dzari'ah - Nabilatun Nada; M Lathoif Ghozali (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The study aims to analyze the boycott behavior of Zionist Israeli products according to MUI Fatwa No. 83 of 2023 from the perspective of sadd al-dzari'ah. With the perspective of sadd al-dzari'ah, the boycott of Israeli products is a form of minimizing the harm received by Palestinian Gaza and supporting Palestinian independence by crippling their economy. Researchers used library research method with qualitative approach and descriptive analysis technique. Then the data sources were obtained from MUI Fatwa No. 83 of 2023 as primary data and reference sources from journals through scientific articles, books, & mass media related to secondary data sources relevant in the research. The result of the research is that the act of boycotting Israeli products must be done and is a recommendation from the MUI fatwa to fight for Palestinian independence. With the MUI fatwa on boycotting Zionist products, using sadd al-dzari'ah, which is to close the way so that Israel does not continue the massacre of Gaza because it is an act of dharar and for the sake of benefit (common good) to uphold the value of humanity and solidarity between Muslims. Furthermore, researchers use the perspective of sadd al-dzari'ah as a scholarly ijtihad to explore phenomena on the basis of Islamic law.Keywords: Product Boycott, MUI Fatwa, Saddudz Dzari'ah, Palestine.